The moderation of innovation on the relationship between market orientation and firm performance - Mohd Yusof, Sitinor Wardatulaina (2021)
Rapid changes in globalization trends demand manufacturers to improve quality, serviceability and versatility, in order to stay competitive in the manufacturing industry. Broadly, Malaysia's manufacturing industry has expected to grow and expand to stay relevant and compete in this competitive environment. As a reward, Malaysia is likely to benefit from these trends, although robust domestic demand and attractive external demand fuel investment growth during speedy recovery in developed economies and faster growth prospects in the nation. Furthermore, innovation has been proved to add advantage and contribute to the success of a firm. Meanwhile, manufacturers need to clearly understand their market orientation through their customer needs and wants, competitor strategy and as well as delivering excellent firm performance. From the following circumstances, this study aimed to explore the impact of market orientation and innovation on firm performance in the manufacturing sectors in Malaysia. Additionally, the researcher also determines to examine the impact of innovation as the moderator towards the relationship of market orientation and firm performance. Extensive literature showed that market orientation consists of cultural and behavioral concepts, and through MKTOR and MARKOR measurement, customer orientation, competitor orientation, inter-functional coordination, intelligence generation, intelligence dissemination and organizational responsiveness were identified as the independent variables. At the same time, firm performance was selected as the dependent variable. In order to meet the research objectives, this study employed a quantitative method by conducting self-administered survey questions and stratified random sampling to 321 manufacturers. The distribution of questionnaires was conducted by hand and through electronic mail. The same method was applied in data collection. The results from correlation, multiple regression and hierarchical regression have identified that market orientation significantly affects firm performance. Cultural components as the elements of market orientation showed significant results, although another component which is the behavioral element, showed an insignificant result. The dimensions of cultural components; competitor orientation and inter-functional coordination, showed significant results, whereas customer orientation and competitive action showed insignificant results. Dimensions of behavioral components, which are intelligence generation and intelligence dissemination, significantly impact the performance. Meanwhile, organizational responsiveness showed an insignificant impact. Innovation, on the other hand, showed to be effective in moderating the impact of market orientation towards performance. The study contributes to the body of knowledge by examining the combination of both components of market orientation which are cultural and behavioral aspects and as well as the moderating roles of innovation. Secondly, it complements the market orientation theory regarding the interconnection between innovation and performance. In conclusion, this study provided a clearer understanding of market orientation and innovation practiced by manufacturers in Malaysia and offer several implications for research, policymakers, and practitioners.